Biomimetic-Inspired Infrared Sensors from Zn3P2 Microwires: Study of Their Photoconductivity and Infrared Spectrum Properties. (26th June 2014) - Israelowitz, M.; Weyand, B.; Leiterer, C.; Munoz, V.; Martinez-Tomas, C.; Herraiz-Llacer, M.; Slowik, I.; Beleites, C.; Fritzsche, W.; Krafft, C.; Henkel, T.; Reuter, M.; et al.
Abstract : The fire beetle, Melanophila acuminata (Coleoptera: Buprestidae), senses infrared radiation at wavelengths of 3 and 10–25 microns via specialized protein-containing sensilla. Although the protein denatures outside of a biological system, this detection mechanism has inspired our bottom-up approach to produce single zinc phosphide microwires via vapour transport for IR sensing. The Zn3 P2 microwires were immobilized and electrical contact was made by dielectrophoresis. Photoconductivity measurements have been extended to the near IR range, spanning the Zn3 P2 band gaps. Purity and integrity of the Zn3 P2 microwires including infrared light scattering properties were confirmed by infrared transmission microscopy. This biomimetic microwire shows promise for infrared chip development.